2018
DOI: 10.4103/abr.abr_133_17
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-containing versus Clarithromycin-containing Therapy for Helicobacter pylori Eradication: A Prospective Randomized Controlled Clinical Trial

Abstract: Background:This study evaluated the clinical efficacy and tolerability of a 14-day course of bismuth-based quadruple therapy including tinidazole and levofloxacin in compare to a 14-day bismuth-based quadruple therapy including clarithromycin as first-line treatment for Helicobacter pylori infection in Iranian adults.Materials and Methods:The study was a prospective, parallel group, randomized controlled, clinical trial that conducted on 150 patients with H. pylori infection. Patients were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, studies conducted in other parts of Iran revealed uoroquinolone-containing regimens including a 14-day of omeprazole, levo oxacin (250 mg twice a day) and amoxicillin as well as a 14-day of omeprazole, levo oxacin (500 mg twice a day), and amoxicillin as rescue therapies of H. pylori had eradication rate of 90 % and 86.7 %, respectively [43,44]. Moreover, there are some other Iranian investigations that evaluated the e cacy of levo oxacin-based, sequential therapy in the treatment of H. pylori, and the eradication rate ranged from 70.8% to 85.1 % [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies conducted in other parts of Iran revealed uoroquinolone-containing regimens including a 14-day of omeprazole, levo oxacin (250 mg twice a day) and amoxicillin as well as a 14-day of omeprazole, levo oxacin (500 mg twice a day), and amoxicillin as rescue therapies of H. pylori had eradication rate of 90 % and 86.7 %, respectively [43,44]. Moreover, there are some other Iranian investigations that evaluated the e cacy of levo oxacin-based, sequential therapy in the treatment of H. pylori, and the eradication rate ranged from 70.8% to 85.1 % [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated the eradication rate of levo oxacin-containing regimens was not associated with age [45,47,44], gender [46,45,44], smoking status [48,45], and education level [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies conducted in other parts of Iran revealed uoroquinolone-containing regimens including a 14-day of omeprazole, levo oxacin (250 mg twice a day) and amoxicillin as well as a 14-day of omeprazole, levo oxacin (500 mg twice a day), and amoxicillin as rescue therapies of H. pylori had eradication rate of 90% and 86.7%, respectively [43,44]. Moreover, there are some other Iranian investigations that evaluated the e cacy of levo oxacin-based, sequential therapy in the treatment of H. pylori, and the eradication rate ranged from 70.8% to 85.1% [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…No relationship was observed between patient demographic characteristics including age, gender, cigarette smoking, and alcohol drinking and the success rate of both BPAL-7 and PBAL-10 regimens. Previous studies have also demonstrated the eradication rate of levo oxacin-containing regimens was not associated with age [45,47,44], gender [46,45,44], smoking status [48,45], and education level [45].…”
Section: Discussionmentioning
confidence: 99%
“…I read with a great interest the article titled, “Levofloxacin-containing versus clarithromycin-containing therapy for Helicobacter pylori eradication: A prospective randomized controlled clinical trial”[ 1 ] authored by Sebghatollahi et al . I would like to compliment the authors for conducting a study on a widely prevalent disease with a very good design.…”
mentioning
confidence: 99%